After we transgress God’s values: relational spirituality as a paradigm for the Christian experience of reconciliation with God - Cook, Kaye V.; Cowden, Richard G. (Frontiers in Psychology, 2025)
In the Christian spiritual journey, the desire for communion with God is sometimes challenged by personal sin—instances in which the believer transgresses God’s standards or values for how they ought to live. Thus, the need for divine forgiveness is an important concept in Christianity. To date, relatively little research has explored Christian experiences of forgiveness from God for personal sin, the factors that shape those experiences, and the effects of experiencing forgiveness from God on different aspects of their life. To support the development of research in this area, this paper proposes a relational spirituality model of personal sin for conceptualizing how a network of interrelated cognitive-affective appraisals involving the self, the personal sin, God, and other people can shape a Christian’s experience of, response to, and resolution of personal sin. We introduce the core elements of the model and explore how the interrelations among these elements might influence a Christian’s relational experience with God following recognition of a personal sin. We discuss the unique contributions of the model to the psychological literature on divine forgiveness and highlight implications of the model for advancing research on Christian experiences of forgiveness from God.